A multiauxotrophic CHO cell line for the rapid isolation of producers of diverse or high levels of recombinant proteins. Issue 6 (19th March 2022) - Zhang, Qinghao; Jiang, Bo; Nelson, Luke; Huhn, Steven; Du, Zhimei; Chasin, Lawrence A.
Abstract: Chinese Hamster Ovary (CHO) cells are widely used for the high‐level production of recombinant proteins. We created a multiauxotrophic mutant of CHO‐K1 cells, CHO8A, that is deficient in eight enzymatic steps in the purine/pyrimidine biosynthetic pathways. Prototrophy was restored by transfections with complementary DNA‐based genes for the eight missing activities. CHO8A cells permit: (1) selection of transfectant clones that have incorporated genes for eight or more different polypeptides, suitable for engineering complex proteins, or pathways; and (2) the single‐step selection of high producers of a particular protein. The latter is achieved by simultaneous use of eight vectors, each bearing one of the eight rescue genes and a cargo protein gene. Screening as few as 10 surviving colonies yielded high producers secreting mAbs at 84 picograms per cell per day or more. CHO8A was isolated by CRISPR‐Cas9 knockout of 10 genes in the pathways to pyrimidines ( Dhodh, Umps, Ctps1, Ctps2, and Tyms ) and purines ( Paics, Atic, Impdh1, Impdh2, and Gmps) . Abstract : Zhang et al. have created a multiauxotrophic mutant of CHO‐K1 cells in which eight steps in the biosynthetic pathways to purines and pyrimidines have been knocked out. These cells, named cell line CHO8A, grow well when provided with hypoxanthine, guanine, uridine, cytidine, and thymidine or if transfected with a complete set of eight vectors that restore the missing enzymatic steps. Cotransfection with such vectors that also carry antibody heavy or light chains yield cell lines that are high monoclonal antibody producers (e.g., >50 picograms per cell per day) in a single step that demands the incorporation of the complete set of vectors.